A Balanced and Broad Approach to Technological Innovations - Quinet, Félix (Relations industrielles / Industrial Relations, 1968)
Collective bargaining is a process on which technological change might not only have an impact but a process that should be strengthened through its responses to technological change.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z